Effect of alpha amylase on early childhood caries: a matched case-control study - Farzad Mojarad; Samira Fazlollahifar; Jalal Poorolajal; Mehrdad Hajilooi (Brazilian Dental Science)
Objectives: There are a few studies addressing the relationship between salivary alpha-amylase and dental caries. This study was implemented in order to investigate the effect of salivary alpha-amylase level on early childhood caries (ECC).